DISTINCTIVE FEATURES OF MALAYSIAN SOCIETY MODERNIZATION (European Journal of Interdisciplinary Research and Development, 2025)
In this article analyzes the historical features of modernization of Malaysia. Also covers the process of forming a model of the development of Malaysia and the factors influencing it.